2016
DOI: 10.1063/1.4941158
|View full text |Cite
|
Sign up to set email alerts
|

Using problem-based learning to improve students’ creative thinking skills on water purification

Abstract: Abstract. The aim of this study is to obtain information about the using Problem-based Learning (PBL) to improve students' creative thinking skills on water purification. The research adopted quasi-experimental method with one group pre-test-post-test design, involving 31students of class XI in one SMK in Cimahi as the subjects of study. The students were divided into three groups categories: high, medium, and low based on the average grades of daily tests. The used instruments in this study were essay, observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 14 publications
4
8
0
Order By: Relevance
“…This is in line with the research [13], [19], [10] and [20]. CTA gain was better because PBL activities tend to invite student's to learn more actively.…”
Section: The Average Gain Of Students' Creative Thinking Ability Taugsupporting
confidence: 78%
See 3 more Smart Citations
“…This is in line with the research [13], [19], [10] and [20]. CTA gain was better because PBL activities tend to invite student's to learn more actively.…”
Section: The Average Gain Of Students' Creative Thinking Ability Taugsupporting
confidence: 78%
“…This study was in line with research [10], [22] concluded that each indicator of creative thinking ability was enhanced after applying PBL model. Student's taught by PBL model had better CTA than conventional learning.…”
Section: The Average Gain Of Students' Creative Thinking Ability Taugsupporting
confidence: 72%
See 2 more Smart Citations
“…In learning activities, creative group students are better to find problems and to solve problems [6]. The students CTA has a great influence in optimizing students thinking processes [7]. This research used CTA variable as moderator to test whether the CTA can support PBL model in improving PSA in physics study.…”
Section: Introductionmentioning
confidence: 99%